Factors that Contribute to Failure Causes of Academically Low Performing Students - Libed, Glenda Demata (SCAD Independent, 2022)
Poor academic performance is identified to be a serious concern that needs to be addressed. To address what caused it, this inquiry was directed by determining the following: 1) respondents' birth order, mental ability, personality, study habits, and reasons of low academic performance; 2) significant difference in students' personality types when grouped according to birth order and mental ability, and 3) significant difference in respondents' study habits when grouped according to mental ability. There were 124 purposively chosen low-performing grade 7 students who are considered respondents of this study. This study made use of descriptive research specifically, the quantitative research method. Findings of the study stated that respondents are mostly middle and firstborn, have the below-average mental ability, extroverted, have low study habits, and mostly prefer studying alone. The topmost reason for low academic performance was “I did not study”. The respondents’ personalities also did not significantly differ regardless of birth order and mental ability. And, they did not significantly differ in study habits regardless of mental ability level. Being mostly extroverts and regardless of mental ability level, they did not study at all which highly explains poor academic performance.